SUPERVISI MENGAJAR PADA PENGEMBANGAN KOMPETENSI GURU DI MADRASAH IBTIDAIYAH WILAYAH TIGA BONE - A, Ardin (JURNAL AL-QAYYIMAH, 2023)
This study aims to describe the learning supervisors carried out by madrasa supervisors for teachers in improving teaching competence in Madrasah Ibtidaiyah Region 3, Bone Regency, 2) Describe the implications of the strategy of madrasa supervisors for increasing class teacher competence in Madrasah Ibtidaiyah Region 3, Bone Regency. This type of research is qualitative using data collection techniques, namely observation, interviews and documentation. The data analysis technique is through the stages of data reduction, data presentation, data verification and drawing conclusions.The results showed that, first, madrasas located in region 3 of Bone Regency tended to carry out learning supervision with three strategies consisting of the planning stages (preparation of supervisory semester programs, preparation of annual supervision programs, preparation of supervision programs/schedules for each school), implementation stages (supervision of equipment learning, supervising the implementation of learning in class, providing the results of a review/assessment of the results of supervision of learning in class) and evaluation stages (student learning outcomes in the form of daily tests, mid semester, and semester tests, results of national exams in arts and sports achievements, attitude achievements ( honesty, discipline, responsibility, cooperation, tolerance and others)). The second result, the implications of the madrasa supervisor's strategy for increasing the competence of class teachers in Madrasah Ibtidaiyah Region 3, Bone Regency, it can be seen that the four competencies (pedagogic, social, personality and professional) have been fostered by the madrasa supervisor. This coaching is carried out when the madrasa supervisor supervises program planning, program implementation and evaluates the results of supervision and fosters the competency of the madrasa supervisor for class teachers in Madrasah Ibtidaiyah in the Bone Regency area. This can be seen from student learning outcomes in the form of increased cognitive test results and changes affective behavior.